The use of games in the classroom to promote mental health knowledge and healthy attitudes in adolescents: a systematic review - Sanabria-Mazo, Juan P.; Pérez-Aranda, Adrián; Armas-Landaeta, Carilene; Royuela-Colomer, Estíbaliz; Mateo-Canedo, Corel; Cabrera-Gil, Itxaso; Monreal-Bartolomé, Alicia; García-Campayo, Javier; López-del-Hoyo, Yolanda (Frontiers in Psychiatry, 2025)
BackgroundMany adolescents face significant mental health challenges, including anxiety, depression, and substance-related and addictive disorders, with a growing need for school-based preventive strategies. Traditional classroom interventions often struggle to engage adolescents, prompting the exploration of game-based approaches to improve mental health knowledge and foster healthier attitudes.ObjectiveThis systematic review evaluates the effectiveness of game-based interventions implemented in classroom settings to enhance mental health knowledge and promote positive attitudes among adolescents.MethodsA comprehensive search was conducted across Medline, PsycINFO, Web of Science, and SCOPUS, yielding 1,152 articles. After screening, 17 studies were included, most using cluster randomized controlled trial designs. These interventions addressed topics of mental health such as substance-related and addictive disorders, anxiety, and depression, employing playful activities like video games, virtual reality simulations, quizzes, and collaborative tasks.ResultsThe interventions showed positive effects on knowledge acquisition and attitude change, with high satisfaction reported by participants. Those programs targeting alcohol and tobacco use were particularly effective in improving knowledge and attitudes. However, the quality of evidence varied, and long-term effects were not widely assessed due to a lack of follow-up in most studies. Some interventions had a limited impact on self-efficacy and behavior change.ConclusionsGame-based classroom interventions show promise in promoting mental health literacy and healthier attitudes among adolescents. While short-term outcomes are encouraging, more rigorous studies with extended follow-up periods are necessary to understand their long-term effectiveness. Future interventions should focus on practical skill development and personalization to maximize impact.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024531914.